Revisiting Benazir Bhutto and her Contribution to Restore Democracy in Pakistan - Azeem, Muhammad (Annals of Human and Social Sciences, 2024)
The main objective of this study is to explore, investigate and analyze the struggle of Benazir Bhutto to restore democracy in Pakistan. Benazir was the daughter of Zulfikar Ali Bhutto, a legendary political leader and Prime Minister of Pakistan who was not only deposed from power in 1977 but was also hanged by the military ruler, Gen. Zia-ul-Haq, in 1979. She chose her father’s path, started her political career and launched a resistance movement (MRD) against an autocratic ruler Gen. Zia and forced him to restore democracy. She was the first Muslim woman in the Muslim world who, by dint of her sheer leadership qualities, rose to the office of Prime Minister twice (1988 and 1993) which is the highest seat of executive office in a democratic system. She had to pass a thorny path of forcing the military dictator to restore democracy in Pakistan.